2021
DOI: 10.1101/2021.02.25.21251531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histopathological assessments reveal retinal vascular changes, inflammation and gliosis in patients with lethal COVID-19

Abstract: Importance: We are in the midst of the human coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2), which is of historic proportions, the likes of which we have not seen in 102 years. Despite being primarily a respiratory virus, COVID-19 can also present with non-respiratory signs, including ocular symptoms as conjunctival hyperemia, chemosis, epiphora, increased secretions, ocular pain, photophobia and dry eye. The virus has also been detected withi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
(54 reference statements)
1
12
0
1
Order By: Relevance
“…Our study does not allow to clearly establish a correlation between the changes we identified in retinal vasculature and the increased risk for thrombotic events known to characterize COVID-19 patients. However, the acute and long lasting modifications to retinal vessels that we were able to observe in COVID-19 could easily be caused or accompanied by an endothelial damage 29 and facilitate blood stasis 19 , two of the three factors of the Virchow’s triad, favoring cloths formation 33 . Further studies are needed to investigate the actual correlation between retinal alterations and thrombotic risk in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Our study does not allow to clearly establish a correlation between the changes we identified in retinal vasculature and the increased risk for thrombotic events known to characterize COVID-19 patients. However, the acute and long lasting modifications to retinal vessels that we were able to observe in COVID-19 could easily be caused or accompanied by an endothelial damage 29 and facilitate blood stasis 19 , two of the three factors of the Virchow’s triad, favoring cloths formation 33 . Further studies are needed to investigate the actual correlation between retinal alterations and thrombotic risk in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 82%
“…In fact, the endothelial activation in COVID-19 correlates with diseases severity 29 and chronic vessels alterations have been documented in patients with severe COVID-19 30 . To further support this theory, recent pathology study on post-mortem eyes from patients who died from COVID-19 reported the presence of retinal vessels walls remodelling 19 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…50 In keeping with the reduction in vessel density in in vivo studies, severely reduced microvascular density has also been reported in retina flat mount from donor eyes from COVID subjects compared to controls, which has led some investigators to propose direct effect of virus infection on endothelial cell damage. 51,52 However, the detection of virus within the retina in post-mortem studies has been inconsistent. In addition to direct effects, hypercoagulation and vasculopathy may also lead to the observed retinal findings.…”
Section: Discussionmentioning
confidence: 99%